NEGOSEIO: framework for the sustainability of model-oriented enterprise interoperability - Coutinho, Carlos Eduardo Dias (2012)
Dissertation to obtain the degree of Doctor of Philosophy in Electrical and Computer Engineering(Industrial Information Systems)